2003
DOI: 10.1037/10464-000
|View full text |Cite
|
Sign up to set email alerts
|

Determining damages: The psychology of jury awards.

Abstract: Determining Damages: The Psychology of Jury Awards is a comprehensive empirical analysis of the reasoning process behind jurors' complex task of deciding damage awards, and how those decision-making processes are sometimes impaired by the structural and procedural elements of civil jury trials. Greene (psychology, University of Colorado, Colorado Springs) and Bornstein (psychology and law, University of Nebraska) move seamlessly from the historical roots of damage awards, to concerns and critiques of jury dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…Despite an accumulating body of research on how jurors make damage awards (for reviews, see Greene & Bornstein, 2003;Hans, 2000;Vidmar, 1998), hedonic damages have received scant empirical attention. What research has been conducted has found that the effect of an injury on a person's lifestyle (i.e., LEL) is strongly correlated with people's (e.g., mock jurors') perceptions of the injury's severity and their noneconomic damage awards (Andrews, Meyer, & Berla', 1996;Wissler, Evans, Hart, Morry, & Saks, 1997).…”
Section: Conducting Research On Hedonic Damagesmentioning
confidence: 99%
“…Despite an accumulating body of research on how jurors make damage awards (for reviews, see Greene & Bornstein, 2003;Hans, 2000;Vidmar, 1998), hedonic damages have received scant empirical attention. What research has been conducted has found that the effect of an injury on a person's lifestyle (i.e., LEL) is strongly correlated with people's (e.g., mock jurors') perceptions of the injury's severity and their noneconomic damage awards (Andrews, Meyer, & Berla', 1996;Wissler, Evans, Hart, Morry, & Saks, 1997).…”
Section: Conducting Research On Hedonic Damagesmentioning
confidence: 99%
“…Research has produced mixed results concerning the effects of jurors' demographic characteristics on verdicts, but generally they only provide a weak or inconsistent influence in both civil and criminal cases (Greene & Bornstein, 2003). Of course, when age is examined in jury studies it is commonly in reference to a student versus a non-student sample of mock jurors (Bornstein, 1999) and not based on comparisons of the elderly versus the non-elderly.…”
Section: Jurorsmentioning
confidence: 99%
“…Compensatory damage awards include economic damages (e.g., medical bills, lost work) and noneconomic damages (e.g., money for pain and suffering) (for a review, see Greene & Bornstein, 2003). In addition to compensatory damages, most states also allow some form of punitive or exemplary damages against defendants who act in a reckless, willful, or wanton manner (Restatement [Second] of Torts, 1965, §908).…”
Section: Punitive Damagesmentioning
confidence: 99%